The dynamics of social practice everyday life and how it changes - Shove, Elizabeth 1959-; Pantzar, Mika; Watson, Matt (SAGE Publications, 2012)
A clever, innovative book which makes an important contribution to social theory and social policy. An effective introduction, it covers core themes and demonstrates exactly how our everyday life is defined by the rise, change and collapse of social practices